Classification of Thinness, Overweight, and Obesity as a Function of the Body Mass Index and Fat Percentiles in Preschool and Primary School Children. Issue 5 (September 2017) - Rodrigues, Jessica; Rocha, Ada
Abstract : Introduction: Portugal is one of the European countries showing an increase in mortality and morbidity associated with chronic diseases, presenting one of the highest prevalence rates of overweight and obesity among children. Objective: The aim of this study was to evaluate the prevalence of thinness, overweight, and obesity as a function of the body mass index (BMI) and fat percentiles in preschool and primary school children in a municipality of the center region of Portugal. Methods: A total of 901 children were evaluated between November 2014 and March 2015. Evaluation included weight, height, waist circumference, and body fatness (total and trunk). Nutritional status was classified based on the Centers for Disease Control and Prevention, BMI percentile by age and gender, and the International Obesity TaskForce (IOTF) cutoff values of BMI. Results: Of the children evaluated, according to the Centers for Disease Control and Prevention cutoff values, 32.3% were overweight or obese, and from those, 16.2% were obese. According to the fat percentile, the prevalence of overweight was 18.0%, corresponding 6.6% to obese children. Total body fat percentage and trunk fat percentage were 23.5% and 17.8%, respectively. Conclusion: The prevalences found were quite different depending on the method used. To allow comparisons and more accurately determine prevalence rates of thinness, overweight, and obesity in children, it is necessary to standardize methodologies between studies and between countries.